The city a collective project: impressions on the Medellín experience (Tempo e Argumento, 2011)
This article addresses the possibility of recreating the idea of a city as a collective project based on the impressions of the ongoing Medellin experience in Colombia. It has been able to create a new urban and citizen-based network due to a new conciliation project where culture is the driver.
Keywords: city of acknowledgment; citys; cultural politics; common culture; civil society; State